Elastic properties of compressed cryocrystals in a deformed atom model: 9th International Conference on Cryocrystals and Quantum Crystals Odessa, Ukraine, September 2–8, 2012 (final part) - Gorbenko, Ie.Ie.; Zhikharev, I.V.; Troitskaya, E.P.; Chabanenko, Val.V.; Pilipenko, E.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
A model with deformed atom shells is built to investigate the elastic properties of rare-gas crystals Ne and Kr under high pressure. It is shown that the observed deviation from the Cauchy relation δ cannot be adequately reproduced with taking into account of only the many-body interaction. The individual pressure dependence δ of isa result of competition of the many-body interaction and the quadrupole interaction associated with the quadrupole-type deformation of electron shells of the atoms during the displacements of the nuclei. Each kind of interaction makes a strongly pressure dependent contribution to δ . In the case of Ne and Kr, contributions of these interactions are compensated to the good precision, providing δ being almost constant against pressure.